Graphic narrative based informed consent for bronchoscopy improves satisfaction in patients after lung-transplantation: A randomized controlled trial. Issue 4 (April 2022) - Seeliger, Benjamin; Kayser, Moritz Z.; Drick, Nora; Fuge, Jan; Valtin, Christina; Greer, Mark; Gottlieb, Jens
Highlights: Bronchoscopy is associated with distress and standard informed consent may be improved. Procedure-specific graphic narratives improve satisfaction with informed consent. A graphic narrative is cost-efficient and feasible to improve patient communication. Addition of graphic narrative did not alter peri-procedural anxiety. Abstract: Objective: This study investigated the effects of supplementing standard informed consent (IC) with a graphic narrative on patient satisfaction, periprocedural anxiety and experience. Methods: Patients due to undergo first conscious surveillance bronchoscopy following lung transplantation were randomized to receive IC with (intervention group) or without (control group) a graphic narrative illustrating the procedure. The primary endpoint was overall patient satisfaction with the IC. Key secondary endpoints were change in state anxiety level, as measured by State Trait Anxiety Inventory, and a questionnaire assessing satisfaction with IC and adverse experience during bronchoscopy (judged by patient and examiners). Results: Sixty patients were randomized, and 59 patients were included in the analysis (30 intervention-group; 29 control-group). Overall patient satisfaction was higher in the intervention group 9.5 ( 25 Q– 75 Q: 8.6–9.8) vs. 8.6 ( 25 Q– 75 Q: 8.1–9.2), p = 0.028). Change in state anxiety level (before vs after informed consent) was similar between the groups. There were no significant differences in adverse experience during bronchoscopy. Conclusion: Addition of a graphic narrative illustrating bronchoscopy improved patient satisfaction with IC but did not influence anxiety before and adverse experience during the procedure. Practice implications: Supplementing the IC process with a procedure-specific graphic narrative may be a simple tool to improve patient satisfaction.